Integrative Analysis of Dog Serum‐Derived CircRNA Expression and Disease Severity, Inflammatory and Cardiac Damage Biomarkers Related to Canine Parvoviral Enteritis - Şükrü Değirmençay; Selçuk Özdemir; Sefa Küçükler; Reyhane Bayat; Muhammed Kadak (Veterinary Medicine and Science)
ABSTRACT Background The tissue‐ and developmental stage‐specific expression of circular RNAs (circRNAs) makes them promising disease biomarkers. CircRNAs play a crucial role in regulating inflammatory responses; however, their function in canine parvovirus (CPV) infection remains largely unexplored. Hypothesis We hypothesized that circRNAs serve as biomarkers for disease severity, inflammation and organ damage in dogs with CPV. Materials and Methods The study included six dogs with mild CPV, six with severe CPV and six healthy controls. Haematological and biochemical parameters were analysed from blood samples. CircRNA profiling in serum samples was conducted through high‐throughput sequencing, followed by bioinformatic analysis to identify potential circRNA biomarkers. Associations between circRNAs and haematological/biochemical markers were examined. Results The severe group exhibited significantly reduced leukocyte counts and elevated C‐reactive protein (CRP) levels (p < 0.05). The mild group demonstrated higher levels of tumour necrosis factor‐alpha (TNF‐α), cardiac troponin I (cTnI) and creatine kinase myocardial band (CK‐MB) (p < 0.05). Thus, the severe group experienced heightened inflammation, whereas the mild group demonstrated increased cardiac damage. Dogs with CPV expressed certain circRNAs differently (upregulated and downregulated), as revealed by gene ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analyses. Eighteen cicRNAs were identified as potential biomarkers. Bioinformatic and correlation analysis revealed that cfa_circ_6789, cfa_circ_6793, cfa_circ_6785, cfa_circ_6798, cfa_circ_6791, cfa_circ_6794 and cfa_circ_3119 could serve as biomarkers of inflammation and disease severity. Conversely, cfa_circ_3114, cfa_circ_3118, cfa_circ_3117, cfa_circ_3113, cfa_circ_3119, cfa_circ_1571, cfa_circ_6786 and cfa_circ_6794 were linked to cardiac damage. Conclusions and Clinical Relevance The identified circRNAs were actively involved in different stages of CPV infection and exhibited strong associations with disease onset and progression. They may play a key role in modulating infection pathogenesis while serving as potential biomarkers for inflammation and cardiac damage. This study is the first to investigate the role of circRNAs in CPV infection, providing novel insights into their diagnostic and prognostic potential.